РЕЗУЛЬТАТИ ДЕРЖАВОТВОРЕННЯ УКРАЇНЦІВ ПОЧАТКУ ХХ ст.: СУЧАСНИЙ ПОГЛЯД І РЕТРОСПЕКТИВА (Zaporizhzhia Historical Review, 2021)
The article presents a brief review of the points of view of the Ukrainian revolution participants and modern historians on the results of the national-liberation struggle of the Ukrainians at the beginning of the ХХ century.